2014
DOI: 10.1136/gutjnl-2013-306144
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening uptake over three biennial invitation rounds in the English bowel cancer screening programme

Abstract: ObjectiveTo examine patterns of colorectal cancer (CRC) screening uptake over three biennial invitation rounds in the National Health Service (NHS) Bowel Cancer Screening Programme (BCSP) in England.MethodsWe analysed data from the BCSP's Southern Hub for individuals (n=62 099) aged 60–64 years at the time of first invitation to screening with a follow-up period that allowed for two further biennial invitations. Data on sex, age and a neighbourhood-level measure of socioeconomic deprivation were used in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 15 publications
15
106
1
1
Order By: Relevance
“…Uptake of screening was higher in our sample (61.0%) than in other studies (von Wagner, Baio, et al, 2011), probably because the age profile meant that the older participants were likely to have been invited over two or more rounds which, as reported recently, can increase uptake (Lo et al, 2014). A recent study using ELSA data, but including a broader age range, found a 57% uptake of screening (Gale, Deary, Wardle, Zaninotto, & Batty, 2015).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Uptake of screening was higher in our sample (61.0%) than in other studies (von Wagner, Baio, et al, 2011), probably because the age profile meant that the older participants were likely to have been invited over two or more rounds which, as reported recently, can increase uptake (Lo et al, 2014). A recent study using ELSA data, but including a broader age range, found a 57% uptake of screening (Gale, Deary, Wardle, Zaninotto, & Batty, 2015).…”
Section: Discussioncontrasting
confidence: 55%
“…The upper age limit is currently being extended to 75. Overall uptake is approximately 54% (von Wagner, Baio, et al, 2011), although rates are higher when several screening rounds are included (Lo et al, 2014). There is evidence of substantial variation in uptake by socio-economic status, with one study finding participation in the most deprived quintile of residential areas to be only 35%, compared with 61% in the least deprived quintile (von Wagner, Baio, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1 Those who attend screening have a 25% reduction (RR 0.75, CI = 0.66 to 0.84) in their risk of death, but only 40% return all three BCSP gFOB kits, although involving GPs in screening increases uptake. 1,2 Faecal immunochemical testing (FIT) measures the globin component of human haemoglobin. Unlike gFOB, FIT does not require dietary restriction, is specific to lower gastrointestinal (GI) cancers as upper GI enzymes degrade human globin, and is less affected by concomitant medication use.…”
Section: Background and Advantages Over Existing Technologymentioning
confidence: 99%
“…These numbers were calculated based on the early experience in the SCREESCO-study and a study of repeated screening in the UK. [96] This means that these two subpopulations will never, respectively always, attend the screening, irrespective of the number of times they were invited to the screening. However, the attendance rate at consecutive invitation to screening was assumed to be the same as at the first invitation to screening.…”
Section: Screening Parametersmentioning
confidence: 99%
“…However, the attendance rate at consecutive invitation to screening was assumed to be the same as at the first invitation to screening. [96,97] The specificity and sensitivity of OC were retrieved from a meta-analysis presented by Telford et al [98] and the corresponding parameters for FIT (cut-off value 10 µg) were obtained from Wijkerslooth et al…”
Section: Screening Parametersmentioning
confidence: 99%